Produção de biossurfactante por Bacillus invictae UCP1617 para formulação de um detergente eco-friendly como aditivo na remediação de petroderivados. - Barata, Maria Inez Campello (2024)
Surfactants are amphipathic molecules that reduce surface and interfacial tension between fluid phases, providing detergency, emulsification and phase dispersion. Most surfactants in industrial use are derived from petroleum; however, interest in microbiological surfactants has increased due to the biodegradability and reduced toxicity of these biomolecules. Therefore, this work aimed to evaluate the production and commercial formulation of a new biosurfactant using the bacterium Bacillus invictae UCP1617. Initially, the production of the biosurfactant was carried out using different combinations of alternative substrates (sugar cane molasses and millet). Then, a complete factorial design was used as a tool to optimize the variables of agitation, temperature, and inoculum size in a mineral medium containing 1.5% corn steep liquor. The best planning condition obtained (agitation of 175 rpm at 28°C and 4% inoculum) was used to scale up biosurfactant production in a 50 L bioreactor. Biosurfactant production in the bioreactor reached a productivity corresponding to 16.70 mg/L/h. The surface tension of the medium was reduced from 69.50 to 30.20 mN/m after 72 hours of fermentation. The biosurfactant was isolated and structurally characterized as a glycolipid and its CMC was determined as 900 mg/L for a surface tension of 29.10 mN/m. The biosurfactant was subjected to stability evaluation under different environmental conditions, being able to form stable emulsions of greater efficiency with engine oil (90.80%) and petroleum (99.00%). The formulation of the biosurfactant to obtain an eco-friendly detergent was carried out with the addition of 0.2% of the stabilizer hydroxyethylcellulose (HEC), 5% fatty acid, and 0.2% potassium sorbate, and the commercial product was stored at 28ºC for 90 days. The formulated biosurfactant maintained the stability of its surface tension at various pHs, temperatures, and NaCl concentrations and presented an absence of toxicity proven by the growth of the seeds of the vegetable cabbage Coração-de-Boi (Brassica oleracea) and cherry tomato (Solanum lycopersicum), as well as the survival of the microcrustacean Artemia salina. The formulated biosurfactant was able to fully disperse the oil in seawater. When placed in clayey soil contaminated with engine oil, the biosurfactant was able to remove, in 24 hours, 99.21% of the oil contained in the soil when used in its CMC. The formulated biosurfactant removed 98.42% of the oil adhered to the glass surface and removed 75.00% of the hydrophobic compound adsorbed to the porous surface in its CMC. Therefore, the commercial biosurfactant produced by Bacillus invictae UCP1617 demonstrates the feasibility of application as an eco-friendly biotechnological additive for remediation processes that consider the preservation and reduction of environmental impacts on ecosystems.